2001
DOI: 10.1038/84948
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Biliverdin IXbeta reductase (BVR-B) catalyzes the pyridine nucleotide-dependent production of bilirubin-IXbeta, the major heme catabolite during early fetal development. BVR-B displays a preference for biliverdin isomers without propionates straddling the C10 position, in contrast to biliverdin IXalpha reductase (BVR-A), the major form of BVR in adult human liver. In addition to its tetrapyrrole clearance role in the fetus, BVR-B has flavin and ferric reductase activities in the adult. We have solved the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 24 publications
4
99
0
Order By: Relevance
“…(17) revealed that the protein structures most closely related to CC3 are members of the SDR family (23). The highest match was with biliverdin IX␤ reductase (20), whereas carbonyl reductase (21, 24) (Fig. 3, b and c) and UDP-galactose epimerase (25) are among the next most closely related structures.…”
Section: Co-crystallization Studies With Potential Cc3 (Tip30)mentioning
confidence: 81%
See 1 more Smart Citation
“…(17) revealed that the protein structures most closely related to CC3 are members of the SDR family (23). The highest match was with biliverdin IX␤ reductase (20), whereas carbonyl reductase (21, 24) (Fig. 3, b and c) and UDP-galactose epimerase (25) are among the next most closely related structures.…”
Section: Co-crystallization Studies With Potential Cc3 (Tip30)mentioning
confidence: 81%
“…CC3 was docked with the C-terminal region of importin ␤2 using FTDOCK (19). The PDB codes for coordinate sets used are as follows: biliverdin IX␤ reductase, PDB code 1HE2 (20); porcine carbonyl reductase, PDB code 1N5D (21); c-AMP-dependent protein kinase catalytic subunit, PDB code 1APM; tat, PDB code 1TBC; and importin ␤2, PDB code 1QBK (22).…”
Section: Cloning Expression and Purification Of Cc3 (Tip30)-mentioning
confidence: 99%
“…As for the crystal structures of E. coli UDP-galactose 4-epimerase and human biliverdin IX ␤ reductase (BVR-〉), the pyrophosphate group of the modeled cofactor positions itself within hydrogen bonding distance of the amide nitrogens of residues 15 and 16 at the N terminus of the helix, thereby N-capping it and thus compensating for the helix macrodipole (49).…”
Section: Resultsmentioning
confidence: 99%
“…Mutation of one of these three residues, Cys 73 , was reported in one study to cause enzyme inactivation but in another to have no effect on activity (33,34). The crystal structures of rat biliverdin IX␣ reductase (34,35) and human biliverdin IX␤ reductase (36) have been reported. The rat biliverdin IX␣-reductase preferentially binds NADH at lower pH (pH ϳ6.7) but NADPH at higher pH (pH ϳ8.7).…”
mentioning
confidence: 99%